Exporters in the financial crisis - Holger Görg; Marina-Eliza Spaliara (Kiel Institute for the World Economy (IfW), 2014)
Using a large panel of UK manufacturing firms over the period 2000-2009, we consider how firms responded during the most recent financial crisis, estimating models for export market participation decisions and firm growth and survival. The results indicate that financial variables are highly important in predicting export market entry, especially in the midst of the global financial crisis. With respect to firm growth and survival, we find that starters and continuous exporters are more likely to perform well in and out of the crisis than non-exporters.
Keywords: F1; L2; G3; 330; exports; financial crisis; financial health